Anti-proliferative Activity of Some Oleanolic Acid Derivatives with Potent Topoisomerase Inhibitory Activity on B16 Melanoma Cells - Ahmed Ashour; Ryuichiro Kondo; Kuniyoshi Shimizu (Wood Research Journal, 2018)
Our previous study included the semisynthetic reactions on oleanolic acid, a common wood-derived oleanane-type triterpene. Ten rationally designed derivatives of oleanolic acid were synthesized based on docking studies and tested for their topoisomerase I and IIα inhibitory activity. Semisynthetic reactions targeted C-3, C-12, C-13 and C-17. Some of these compounds act as dual inhibitors for both topoisomerase I and IIα giving new anticancer agents. The cytotoxic activity of these compounds on B16 melanoma cancer cells was evaluated. Results showed that most of these compounds have a higher cytotoxic activity on B16 melanoma cells.